Mid-infrared plasmonic multispectral filters - Wang, Ang (Sci Rep, 2018)
A miniaturized mid-infrared spectral analyzer will find a wide range of applications as a portable device in non-invasive disease diagnosis, environmental monitoring, food safety and others. In this work, we report an integrated spectral analyzer that can be constructed by using Au subwavelength hole arrays as multispectral filters. The hole arrays were fabricated with CMOS compatible processes. The transmission peak of the subwavelength hole arrays is continuously tuned from 3 μm to 14 μm by linearly increasing the periodicity of the holes in each array. Fourier transform infrared (FTIR) microscopy was applied to spatially map out the transmission of the hole arrays. The results show that each hole array can selectively allow for transmission at a specific wavelength. We further constructed an IR spectral analyzer model based on the microhole multispectral filters to retrieve IR spectral information of two test samples. Our experimental results show that the spectra from the integrated spectral analyzer follow nearly the same pattern of the FTIR spectra of the test samples, proving the potential of the miniaturized spectral analyzer for chemical analysis.